Hubungan Posisi Tidur dengan Tekanan Intra Okular pada Pasien Glaukoma - Agatha Catherine; Rodiani; Risti graharti (Medula, 2023)
Glaucoma still be the second most common cause of blindness in the world. Glaucoma is a group of neuropathic diseases of the optic nerve which is characterized by the extraction of the optic disc (cupping) may causes visual disturbances. Intraocular pressure (IOP) is the most influential factor of glaucoma and affected by various factors, especially body position during sleep. Sleep composed of REM sleep and NREM sleep is related to muscle tone and psychological activity that has impact for sleep posture. The increase of intraocular pressure is directly proportional to the increase of episcleral venous pressure. The increase of IOP in prone position is probably due to an increase in choroidal vascular volume and increase of episcleral venous pressure, whereas in the lateral decubitus position the increase in IOP is caused by compression of the jugular veins when using a pillow. IOP rises when move to the lateral decubitus position in the dependent eye was 1 mmHg and in the non-dependent eye was 2 mmHg. The angle of the head to the bed has an effect on increasing IOP, in the vertical head-down position there can be an increase of 70% due to the force of gravity, whereas in patients who sleep with their head at a higher angle to the mattress, the IOP will decrease compared to the horizontal sleeping position.